Enhancing Students' Mathematical Problem-Solving Skills through Problem-Based Learning - Saniah Afiqoh; Aline Dorimana; Abdul Halim (Gema Cendekia Institute, 2026)
This study aimed to explore the effectiveness of Problem-Based Learning (PBL) in enhancing students' mathematical problem-solving abilities in secondary schools. A quasi-experimental design employing Classroom Action Research (CAR) was conducted in several secondary schools in Indonesia and Rwanda. Data were collected through problem-solving tests, observation, and documentation. Results demonstrated that PBL implementation significantly increased average problem-solving scores from 47.11 to 88.57 after two cycles of intervention. Qualitative observations indicated enhanced student engagement, critical thinking, and collaborative skills. PBL also promoted learning motivation, concept mastery, and student autonomy in tackling mathematical problems. These findings provide practical implications for developing an active and participatory mathematics curriculum.